2008
DOI: 10.1038/jp.2008.7
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance air medical transport of extremely low birth weight infants with pneumoperitoneum

Abstract: Objective: Long-distance air transport (LDAT) of infants with pneumoperitoneum for pediatric surgical evaluation has not been previously reported. We examined whether extremely low birth weight (ELBW) infants with and without pneumoperitoneum would tolerate transport differently.Study Design: A retrospective cohort study was conducted comparing ELBW infants diagnosed with pneumoperitoneum to other ELBW infants transported >2000 miles by a trained team from a US Department of Defense tertiary care neonatal inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…They showed that male newborns were dominant both in the group with pneumoperitoneum and the one with the babies without pneumoperitoneum. The birth weight of the patients with pneumoperitoneum was higher compared to the group of patients who did not suffer from it, whereas at the time of transport the infants without pneumoperitoneum were older and had higher body weight compared to the infants with pneumoperitoneum [33]. According to the authors' own study, the preterm infants were older at the time of transport, whereas the group of full-term newborns was characterized by a higher body weight during transport and a more severe clinical condition on the basis of NACA scale.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…They showed that male newborns were dominant both in the group with pneumoperitoneum and the one with the babies without pneumoperitoneum. The birth weight of the patients with pneumoperitoneum was higher compared to the group of patients who did not suffer from it, whereas at the time of transport the infants without pneumoperitoneum were older and had higher body weight compared to the infants with pneumoperitoneum [33]. According to the authors' own study, the preterm infants were older at the time of transport, whereas the group of full-term newborns was characterized by a higher body weight during transport and a more severe clinical condition on the basis of NACA scale.…”
Section: Discussionmentioning
confidence: 79%
“…Studies on the importance of neonatal stabilization of critically ill newborns during transport carried out by Xu et al (2019) showed that the study group of high risk of transported neonates was dominated by male patients whose average gestational age was 32.63 weeks and body weight was 1828.7 g. The control group of high-risk transported newborns was equal in terms of gender distribution, and the average gestational age was higher, 34.89 weeks, as well as body weight, 2397 g [32]. McAdams et al (2008) presented studies on long-distance airborne transport of infants with very low birth weight and pneumoperitoneum. They showed that male newborns were dominant both in the group with pneumoperitoneum and the one with the babies without pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…Individual risk-benefit assessments must be taken into account balancing inherent transport risks with the patient's clinical condition and locally available resources. 11,[18][19][20] The preterm infants in this series were transported at a median age of 35.5 days (range ¼ 7-150 days), with a trend toward earlier transport in less premature babies. The first 5 days of life, shown to carry the highest risk of death in premature infants, have been avoided in all infants.…”
Section: Discussionmentioning
confidence: 91%
“…There is limited, if any, data on international, long-distance, pediatric aeromedical transports. 3 4 5 6 7 8 9 10 11 In this paper we report demographics and transport characteristics of a large group of children and neonates that have been transported by international fixed-wing air ambulance by a European air ambulance company over a 5-year period. This retrospective, observational study aimed to investigate the feasibility and outcomes of international, long-distance aeromedical transport of neonates and children by analyzing transport-associated therapy escalations, autoevaluated transport outcomes, and occurrences of adverse events (AE) en-route.…”
Section: Introductionmentioning
confidence: 99%
“…Short-distance neonatal transfers occur frequently for unwell neonates requiring tertiary-level care, however longer distance (>2500 km), neonatal transfers are less common in Australia and Internationally. While some data are emerging in this field, [4][5][6][7][8] there is minimal data reported on demographic, clinical and biochemical parameters of these patients during transport and on arrival. Interstate aeromedical neonatal transfers from Royal Darwin Hospital require greater than 4 h of flight time and therefore represent a unique clinical patient group.…”
Section: What This Paper Addsmentioning
confidence: 99%